MEDICAMENTOS ORAIS MODIFICADORES DA DOENÇA DISPONÍVEIS NO SUS PARA TRATAMENTO DE ESCLEROSE MÚLTIPLA: EFETIVIDADE E SEGURANÇA NO CONTEXTO DE VIDA REAL - Cristiane Munaretto Ferreira (2025)
Introduction: Fingolimod, teriflunomide and dimethyl fumarate were the first oral therapeutic options for managing multiple sclerosis, an autoimmune, inflammatory and degenerative disease of the central nervous system. Objective: Analyze the clinical effectiveness and safety of oral disease-modifying drugs available in the Brazilian Unified Health System for the treatment of multiple sclerosis. Method: This was an observational, prospective and longitudinal study involving patients treated under the Specialized Component of Pharmaceutical Assistance in Mato Grosso do Sul with teriflunomide, dimethyl fumarate or fingolimod. Data were collected over two years through interviews and health record reviews every six months. The outcomes assessed were the effectiveness of the medications on clinical and radiological parameters of disease, adherence by verifying the medication possession ratio and the Morisky-Green Test, satisfaction by the Treatment Satisfaction Questionnaire for Medication©, safety and discontinuation of medication treatment at follow-up. The database and statistical analyses were performed using the SPSS (Statistical Package for Social Sciences, version 22.0 for Windows) and PRISM (GraphPad Software, version 5.01 for Windows) statistical programs. The significance level adopted was α = 5% for all static tests performed. Results: A total of 107 patients were included, with a median age of 43 years (32 - 52); 72.0% were female, and 79.4% self-identified as white. The relapsing-remitting phenotype was predominant (90.7%), and 80.4% of the cohort was being treated with fingolimod. Patients on teriflunomide were older (p=0.029) and had longer disease duration compared to those receiving dimethyl fumarate (p=0.048). Fingolimod showed an increase in the annual flare rate between the first and second year of follow-up (0.09 ± 0.48 and 0.16 ± 0.49, p=0.044). The majority of treated with fingolimod (67.1% and 74.6%) and teriflunomide (60.0% and 75.0%) achieved no evidence of disease activity at the end of the follow-up periods. The proportion of adherents to treatment with fingolimod, according to the medication possession ratio, remained high during the first and second year of follow-up (84.9% and 82.9%). As for the Morisky-Green test, adherence to fingolimod was higher than 68.0% at all the times analyzed. High satisfaction levels were reported across all domains of the Treatment Satisfaction Questionnaire for Medication©. The increase in satisfaction scores for the effectiveness (p